2007
DOI: 10.1007/bf03173652
|View full text |Cite
|
Sign up to set email alerts
|

The influence of a teacher research experience on elementary teachers’ thinking and instruction

Abstract: The purpose of this study was to investigate whether and how elementary teachers' thinking and instruction changed as a result of a teacher research experience. Each teacher worked with a scientist conducting research for a period of six weeks. Data in the form of classroom observations and interviews was collected before and after the research experience. Also, document analysis of journals kept during the research experience was conducted. Case studies for three elementary teachers describe the specific chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 18 publications
3
28
0
5
Order By: Relevance
“…In this sense, our findings are in line with the studies that have reported that reflection-on-action develops teachers´ awareness (Schussler, Stooksberry & Bercaw, 2010), that it triggers transformations of teachers´ beliefs and points of view, as well as teacher´s instruction (Dixon & Wilke, 2007;Freedman, Bullock & Duque, 2005;Kabilan, 2007;Kang, 2007;Kucan, 2007;Manrique & Borzone, 2012;Manrique, 2013;Pareja Roblin & Margalef, 2013;Schussler, 2006;Schussler, Stooksberry & Bercaw, 2010). Our findings also show the power of video analysis, that can enable teachers a unique opportunity to review and reflect on their positioning and it can foster changes in practices (Bower, Cavanagh, Moloney & Dao, 2011;Charteris & Smardon, 2013;Danielowich, 2014;Henessya & Deaneya, 2009;Kersting, Givvin, Sotelo & Stigler, 2010;Santagata & Angelici, 2010).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In this sense, our findings are in line with the studies that have reported that reflection-on-action develops teachers´ awareness (Schussler, Stooksberry & Bercaw, 2010), that it triggers transformations of teachers´ beliefs and points of view, as well as teacher´s instruction (Dixon & Wilke, 2007;Freedman, Bullock & Duque, 2005;Kabilan, 2007;Kang, 2007;Kucan, 2007;Manrique & Borzone, 2012;Manrique, 2013;Pareja Roblin & Margalef, 2013;Schussler, 2006;Schussler, Stooksberry & Bercaw, 2010). Our findings also show the power of video analysis, that can enable teachers a unique opportunity to review and reflect on their positioning and it can foster changes in practices (Bower, Cavanagh, Moloney & Dao, 2011;Charteris & Smardon, 2013;Danielowich, 2014;Henessya & Deaneya, 2009;Kersting, Givvin, Sotelo & Stigler, 2010;Santagata & Angelici, 2010).…”
Section: Discussionsupporting
confidence: 89%
“…Numerous studies have reported that the process of reflection-on-action can play a vital role in fostering transformations of teachers´ beliefs, points of view, knowledge and strategies (Dixon & Wilke, 2007;Eilam & Poyas, 2009;Freedman, Bullock & Duque, 2005;Kabilan, 2007;Kang, 2007;Kucan, 2007;Manrique & Borzone, 2012;Pareja Roblin & Margalef, 2013;Schussler, 2006;Schussler, Stooksberry & Bercaw, 2010). For instance, Schussler, Stooksberry and Bercaw´s analysis of teachers´ dispositions in 35 teaching journals in U.S.A shows that those teachers who possessed the greatest awareness of their dispositions also showed a propensity to unpack their assumptions, adopting multiple perspectives, questioning the how and why of their thinking and actions and balancing the focus on students and the focus on the self.…”
Section: Teacher Education and Teacher Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although RETs have become a common approach to science teacher PD, and one that has received a great deal of support in the United States from organizations such as the National Science Foundation (NSF), research into the effectiveness of these programs as catalysts for modifying teacher practice is limited (Blanchard et al, 2008;Capps et al, 2012;Dixon & Wilke, 2007;Hughes, Molyneaux, & Dixon, 2012;Pop, Dixon, & Grove, 2010). Much of the earlier work following teacher PD programs has been based on teacher self-report, although more recent work into RETs has begun to systematically focus on changes in teacher thinking (Dixon & Wilke, 2007;Schwartz, Weserlund, Garcia, & Taylor, 2010), teacher practice (Blanchard et al, 2008;Hughes et al, 2012;Pop et al, 2010), and subsequent student achievement (Silverstein, Dubner, Miller, Glied, & Loike, 2009). The research presented here follows this more recent tradition as it examines the effectiveness of two different forms of the RET programs in shaping teacher beliefs, affect, and practice to identify the most essential aspects of such programs to support teacher learning.…”
Section: Introductionmentioning
confidence: 99%
“…En términos generales, es de resaltar la tendencia que sobre este particular se ha encontrado en otros estudios (Dixon y Wilke, 2007;Gotzens, et al, 2007). Los docentes acostumbran a otorgar mayor preponderancia a las infracciones que denominamos de tipo convencional, que a las de tipo instruccional, a pesar de que aun siendo ambas importantes para el orden y funcionamiento del aula, las instruccionales resultan imprescindibles para el cabal desarrollo del proceso de enseñanza-aprendizaje, además de ser las que los profesores pueden gestionar y modificar de forma directa (Gotzens, et al, 2007).…”
Section: Disciplina Escolarunclassified